'The biggest gang'? Police and people in the 2011 England riots. (12th February 2018) - Newburn, Tim; Diski, Rebekah; Cooper, Kerris; Deacon, Rachel; Burch, Alex; Grant, Maggie
ABSTRACT: Conflict with the police is a staple of civil disorder and the English riots of 2011 were no exception. The antagonism towards the police expressed by the rioters varied in intensity – from a low-level anger stemming from occasional negative experiences on the one hand to outright, visceral hostility on the other – but was visible everywhere riots took place. Leading politicians dismissed this hostility as nothing more than the typical wariness criminals have of the police. Indeed, it is undoubtedly the case that the police are an easy target for rioters seeking to explain away their conduct. Nevertheless, drawing on 270 interviews with people involved in the riots this paper shows that for some involved the police were a very deliberate and specific focus of anger and resentment. The basis of such feelings was complex and variable, but included historically poor relations between the police and particular communities, an inherited distrust of the police as an institution, to more particular and immediate experiences of mistreatment and prejudice – often coalescing around the perceived misuse of police powers such as stop and search.